Misunderstanding and misapplication of motor insurance law: will the Supreme Court come to the rescue? - Marson, James; Ferris, Katy (EJoCLI, 2017)
For many years a tension has existed between the law of the European Union governing motor vehicle insurance and the UK’s transposition, interpretation and application of its national law. Cases including Delaney v Pickett & Tradewise [2011] EWCA Civ 1532 and EUI v Bristol Alliance Partnership[2012] EWCA Civ 1267 have demonstrated the UK’s misunderstanding of its legal obligations in this area and has led to the award of damages to affected individuals against the UK. On 5 December 2016 the Court of Appeal issued its judgment in the case Sahin v Havard and Riverstone Insurance (UK) Ltd [2016] EWCA Civ 1202. The Court was tasked to apply provisions of the Road Traffic Act 1988 to a victim of an unauthorised driver in a claim against the policyholder and the insurer. It is argued here that the Court has misunderstood and misapplied the EU parent law in its application of national law. The case may ultimately be determined by the Supreme Court but it is a ruling of sufficient significance in its lack of adherence to EU law and, given the notoriety of cases demonstrating the inconsistencies of the Court of Appeal’s decisions in motor vehicle insurance law, it is worrying that these judgments seemingly have been ignored. The ruling also has important implications for the consequences that Brexit will have on motor vehicle insurance. This is particularly if, as is expected, the UK pursues a ‘hard Brexit’ without access to the single market and the need to comply with the free movement principles through which the motor vehicle insurance directives are based. The UK would therefore be freed of the compatibility issues demonstrated in Sahin, but this will likely leave third party victims in a weaker position.